New technologies for future living. A proposal for 2100s Milan - Paola Marrone; Claudio Piferi; Antonello Monsù Scolaro; Elisa Belardi; Manuela Demurtas; Maria Grazia Giardinelli; Federico Orsini; Valentina Santi; Andrea Sichi (Agathón)
Evolutionary dynamics and the current environmental, social and economic emergencies envisage new urban visions requiring designers to shift the reference time’s horizon towards long-period scenarios. The contribution refers to this context with the aim to investigate future inhabiting presenting the results of a design experience of urban regeneration led in Milan for RELIVE 2019 competition. The project draws inspiration from last century’s utopian cities visions and is developed based on an Amplified Requirements Framework projected towards long-term scenarios. The design proposal integrates traditional tools and technologies with the new possibilities offered by Key Enabling Technologies prefiguring a replicable model for a resilient, inclusive and low-environmental impact city.